2010
DOI: 10.1111/j.1465-7295.2009.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Disclosure Policies: Evidence From the Electricity Industry

Abstract: A "third wave" of environmental policy has recently emerged that emphasizes information provision as an integral part of the risk mitigation strategy. While theory suggests that information programs may correct market failures and improve welfare, the empirical effectiveness of these programs remains largely undetermined. We show that mandatory information disclosure programs in the electricity industry achieve stated policy goals. We find that the average proportion of fossil fuels decreases and the average p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 47 publications
3
71
0
Order By: Relevance
“…One is work concerned with the role of signals in informing consumer choice within settings where potential consumers find it difficult to judge quality (Daughety and Reinganum, 2008;Dranove and Jin, 2010;Nelson, 1970;Spence, 1973). Our findings add to a growing body of literature which investigates how consumer demand is affected by standardised quality indicators provided by external parties in areas such as schooling (Hastings and Weinstein, 2008), health care (Cutler et al, 2004;Werner et al, 2012) and the environment (Delmas et al, 2010). Additionally, the article is instructive for recent debates in economics about salience, and the propensity of market actors to pay disproportionately more attention to information presented in some formats than others (Chetty et al, 2009;Falkinger, 2008;Hirshleifer and Teoh, 2003).…”
Section: Introductionmentioning
confidence: 61%
“…One is work concerned with the role of signals in informing consumer choice within settings where potential consumers find it difficult to judge quality (Daughety and Reinganum, 2008;Dranove and Jin, 2010;Nelson, 1970;Spence, 1973). Our findings add to a growing body of literature which investigates how consumer demand is affected by standardised quality indicators provided by external parties in areas such as schooling (Hastings and Weinstein, 2008), health care (Cutler et al, 2004;Werner et al, 2012) and the environment (Delmas et al, 2010). Additionally, the article is instructive for recent debates in economics about salience, and the propensity of market actors to pay disproportionately more attention to information presented in some formats than others (Chetty et al, 2009;Falkinger, 2008;Hirshleifer and Teoh, 2003).…”
Section: Introductionmentioning
confidence: 61%
“…Public information has already become a valuable tool in encouraging corporations to behave in a more environmentally friendly manner (see for example Delmas et al, 2009), but it has also been abused in this environment with firms engaging in "green-washing", by reporting only selective information in voluntary disclosure programs (Delmas and Burbano, 2011;Lyon and Kim, 2011). This is a particularly salient issue for the implementation of any consumer-orientated public information program.…”
Section: Resultsmentioning
confidence: 99%
“…Prosocial reputation has been shown to be a significant motivator for charitable donations (Ariely et al, 2009), volunteer firefighting (Carpenter and Caitlin Knowles, 2007), blood donation (Lacetera and Macis, 2010), solar panel purchases (Lessem and Vaughn, 2011;Dastrup et al, 2012) and hypothetical green purchases (Griskevicius et al, 2010). In the corporate world, Jin et al, 2003 found that mandatory hygiene cards positively affected restaurant quality and health outcomes, while Delmas et al (2009) found that mandatory disclosure over utility electricity generation fuel mix percentages resulted in an increase in cleaner fuels. Observability of cooperative behavior has been shown to increase participation in demand response programs allowing the electric utility to remotely restrict the energy consumption during peak hours (Yoeli et al, 2013).…”
Section: Information and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ioannou and Serafeim (2015) finds that firms in four countries (China, Denmark, Malaysia, and South Africa) not only increase disclosure, but also seek assurance of those disclosures and adopt reporting guidelines that increase comparability of disclosed information. Other research reveals that mandatory disclosure programs have forced companies to improve their operating performance relating to the environment (Delmas, Montes-Sancho, and Shimshack 2010) or food and water safety (Bennear and Olmstead, 2008;Jin and Leslie, 2003). However, no research examines investor perceptions of the expected costs and benefits to the announcement of regulations mandating such nonfinancial disclosures.…”
Section: Background and Hypothesis Development Backgroundmentioning
confidence: 99%